Enhancing Hydrogen Storage Properties of MgH2 by Transition Metals and Carbon Materials: A Brief Review - Sun, Ze; Lu, Xiong; Nyahuma, Farai Michael; Yan, Nianhua; Xiao, Jiankun; Su, Shichuan; Zhang, Liuting (Frontiers in Chemistry, 2020)
Magnesium hydride (MgH2) has attracted intense attention worldwide as solid state hydrogen storage materials due to its advantages of high hydrogen capacity, good reversibility and low cost. However, high thermodynamic stability and slow kinetics of MgH2 has limited its practical application. We reviewed the recent development in improving the sorption kinetics of MgH2 and discovered that transition metals and their alloys have been extensively researched to enhance the de/hydrogenation performance of MgH2. In addition, to maintain the cycling property during the de/hydrogenation process, carbon materials (graphene, carbon nanotubes and other materials) have been proved to possess excellent effect. In this work, we introduce various categories of transition metals and their alloys to MgH2, focusing on their catalytic effect on improving the hydrogen de/absorption performance of MgH2. Besides, carbon materials together with transition metals and their alloys are also summarized in this study, which show better hydrogen storage performance. Finally, the existing problems and challenges of MgH2 as practical hydrogen storage materials are analyzed and possible solutions are also proposed.